Antibacterial Activities of Ethyl Acetate Fraction of Methanol Extract From Sosor Bebek Leaves (Kalanchoe pinnata Pers.) - Maulita Cut Nuria; Enny Puji Astuti; Sumantri Sumantri (Universitas Wahid Hasyim, 2010)
Kalanchoe pinnata Pers. is one of the famous herbal in Indonesiathat has been used traditionally to treat diarrhea and dysentery. Akinsulire etal., (2007) proved the antibacterial effects of metanolic extract fromKalanchoe pinnata Pers. leaves, and its sensitive to Gram positive andnegative bacteria. Aims of this research are to find out antibacterialactivities of ethyl acetate fraction of methanolic extract from Kalanchoepinnata Pers. leaves to Gram positive bacteria (Staphylococcus aureus,Bacillus subtilis) and Gram negative bacteria (Pseudomonas aeruginosa,Escherichia coli, Salmonella typhi), to determine Minimum InhibitoryConcentration (MIC) of the fraction, and to find out the active chemicalsubstance of the fraction.Methanolic extract of Kalanchoe pinnata Pers. leaves was made byusing maceration method, then the extract was partitioned gradually byusing hexane, chloroform, diethyl ether and ethyl acetate. Ethyl acetatefraction was examinated in vitro according to turbidimetry methods.Concentrations of the fraction were 256, 192, 160, 128, 96, 64, 32 and 16mg/ml. The active chemical substance of the fraction was identified by ThinLayer Chromatography (TLC) method.The result of this research shows the antibacterial activities of ethylacetate fraction of methanolic extract from Kalanchoe pinnata Pers. leavesboth to Gram positive bacteria and Gram negative bacteria. MIC value ofthe fraction to Gram positive bacteria (Staphylococcus aureus, Bacillussubtilis) is 192 mg/ml, and Gram negative bacteria which are Escherichiacoli ATCC 25922 and Pseudomonas aeruginosa is 192 mg/ml, but the MICvalue to Salmonella typhi is 128 mg/ml. TLC identification show that thefraction contains flavonoid.Keywords : Ethyl acetate fraction of methanolic extract from Kalanchoepinnata Pers. leaves, Antibacterial activity, MinimumInhibitory Concentration (MIC), Flavonoid